HARI AKHIRAT DALAM SURAT AT-TAKWIR (KAJIAN TAFSIR TEMATIK) - Syukri Syukri (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
A careful understanding of the meaning of the content of the Koran, will be found among others the Koran has confirmed that humans do not only live life once. After life in the world there is still another life, namely life in the hereafter. What is explained in the letter at-Takwir turns out to describe various events that occurred on the hereafter. The commentators have different perspectives in understanding the contents of this letter. Fakhru al-Razi for example shows that there is a total correlation of events described in verses 1-13 of the contents of the meaning of verse 14. Meanwhile, Tantawi Jauhari more explicitly details the calcification of the twelve events into six events occurring in the world while the other six events occur after the hereafter. Various events that are judged to be devastating are the images of various terrible events that make humans reflective awareness of the activities he has done